The Role of Teachers' Attitudes Toward Teacher's Efficacy in Education Inclusion in Jakarta Public Elementary School (Indonesian Journal of Learning Education and Counseling, 2019)
Abstract. This study aims to determine the role of teacher attitudes in the dimensions of cognitive, affective, conative towards the efficacy of teachers in inclusive education at the Jakarta Public Elementary School. This study uses quantitative methods with survey approaches and multiple regression techniques, three predictors. The respondents in this study amounted to 143 teachers who taught in Public Elementary Schools in Jakarta who implemented inclusive education, data collection techniques using incidental sampling. The results obtained in this study are teacher attitudes in cognitive, affective and conative dimensions which play a role in teacher efficacy. Abstrak. Penelitian ini bertujuan untuk mengetahui peran sikap guru dalam dimensi kognitif, afektif, konatif terhadap efikasi guru dalam pendidikan inklusi di Sekolah Dasar Negeri Jakarta. Penelitian ini menggunakan metode kuantitatif dengan pendekatan survei dan teknik regresi ganda tiga prediktor. Adapun responden dalam penelitian ini berjumlah 143 guru yang mengajar di Sekolah Dasar Negeri di Jakarta yang mengimplementasi pendidikan inklusi, teknik pengambilan data dengan menggunakan insidental sampling. Hasil yang diperoleh dalam penelitian ini adalah sikap guru dalam dimensi kognitif, afektif dan konatif berperan terhadap efikasi guru.